The Speech of the Twetter: A Linguistic, Sociodiscursive and Sociopragmatic Analysis (2018)
This paper is aimed to characterize and analyze, from linguistic, sociodiscursive and sociopragmatic perspectives, the Twitter messages sent by former Colombian President Ál- varo Uribe Vélez to President Juan Manuel Santos and his Government team (2010-2015), in order to demonstrate the ways in which the enunciator reproduces and legitimates mechanisms of power to influence public opinion. The research was based on the meth- odology of critical discourse analysis (CDA), an interpretive paradigm with a qualitative ap- proach. The results revealed that Uribe’s Twitter messages contain a language loaded with personal, spatial and temporal deictic marks, with particularized conversational implica- tions and discursive strategies, which carry intentions aimed at denouncing and censuring President Santos’ administrative and political decisions and actions. The enunciator, Uribe, authenticates his politico-ideological principles and his past and present actions at the expense of the de-legitimization of his successor and the group of collaborators, since the   purpose is to show that his Government was better and still exercises the power to interfere with criticism and publicly in the political, social and economic affairs of national life and, in turn, influence and gain acceptance of readers and public opinion in general.